Emulsified Fuel: An Alluring Fuel for Power Generation - Harshal Patil; Jyotsna Waghmare (Current Overview on Science and Technology Research Vol. 9, 2022)
Emulsion fuel is an alluring elective fuel that has the potential to reduce particulate emissions in compression ignition engines and stationary engines. In this review, we will discuss different types of emulsion fuel and their working principles. Exceptional accentuation is put on the elements basic to the expected business use of these emulsion fuels. The impact of the fuel on engine performance, durability, and emissions is also taken into account. A critical factor in ensuring fuel compatibility with engines is the formulation of additives to rectify certain key properties and maintain stability. Maintaining vehicle safety with these emulsions, however, may necessitate fuel tank modifications. More research is needed to specify acceptable fuel characteristics, confirm long-term effects on engine durability, and ensure safety in handling and storage. Fuel emulsions are a method of reducing pollutant emissions from the combustion of liquid petroleum fuels. The introduction of this type of fuel onto the market is represented by the selection of fuel emulsions with high stability and improved flow characteristics. The results were helpful for both the consideration of the thermo-chemical properties of the tested fuels and the computations of a chemical equilibrium model.